A Bibliometric Analysis of Themes and Network Structures for Future Research in SMEs Sustainability - Nia Kurniati Bachtiar; Agus Setiawan (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study aims to develop an integrated model of innovation and resilience by examining previous research and identifying opportunities for future research. Design/Methods/Approach: This study interprets the bibliometric analysis report for SMEs' sustainability from 2000 to 2022 based on peer-reviewed journal articles. We used the Scopus database as it is considered to have a broader range of journals. To identify the concept of the relevant topic area, we searched for the article title, abstract, and keywords of journals using keyword combinations' SME' AND 'Sustainability'. We discovered 553 articles, which consist of 1598 authors from 260 journals. Findings: This study discover three clusters based on the bibliometric coupling analysis, which discuss the strategies for SMEs' sustainability. The strategies cover 1) sustainable innovation practice, 2) expanding the role of innovation for sustainable development (from theory to practice), and 3) Supporting SMEs to reach their sustainability. These strategies construct our integrative model for achieving SMEs' Sustainability and develop three stages: early adoption, sustainable-based growth, and full implementation. Along with the identified strategies and model, we also attempt to present two significant elements, innovation and resilience, arguing that both are complementary processes in SMEs' Sustainability. Originality/Value: This research contributes to developing key trends in SME sustainability, delivering key clusters in this topic, and providing an integrative model for sustainability implementation for SMEs. By using bibliometric analysis, such as co-occurrence network, clustering, thematic map, and visualization of state of the art, this study may bring a valuable result in developing the literature by extending the study of innovation and resilience for business sustainability. Practical/Policy implication: The model presented provides a clear process for researchers, managers, and organizations to analyze and adopt the necessary stages to achieve sustainable growth for SMEs. This model is expected to be a practical solution for SMEs to implement a sustainability strategy effectively in their business and promote a sustainable future.